2017
DOI: 10.4103/jets.jets_93_16
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and management of blunt renal injury in children

Abstract: Background:Renal trauma in the pediatric population is predominately due to blunt mechanism of injury. Our purpose was to determine the associated injuries, features, incidence, management, and outcomes of kidney injuries resulting from blunt trauma in the pediatric population in a single level I trauma center.Methods:This was a retrospective chart and trauma registry review of all pediatric blunt renal injuries at a regional level I trauma center that provides care to injured adults and children. The inclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 28 publications
6
17
0
Order By: Relevance
“…Ishida et al [21] found similar findings more recently examining renal trauma injuries in children, with 11.7% having no signs of haematuria. One patient had no haematuria despite high-grade renal injury (Table 2).…”
Section: 4supporting
confidence: 62%
See 1 more Smart Citation
“…Ishida et al [21] found similar findings more recently examining renal trauma injuries in children, with 11.7% having no signs of haematuria. One patient had no haematuria despite high-grade renal injury (Table 2).…”
Section: 4supporting
confidence: 62%
“…Evidence from further studies would suggest that any presentation with macroscopic haematuria following sporting activity, particularly contact sports, mandates full urological investigation as the risk of high-grade renal injury is significant [20][21][22][23][24]. The risk of renal injury with no detectable haematuria varies from 8% to 27%.…”
Section: 4mentioning
confidence: 99%
“…Among the grading classifications, grade IV is described as involvement of parenchymal laceration extending to the corticomedullary junction and the collecting system and vascular injury to the segmental renal artery or vein with contained hemorrhage/hematoma. [27][28][29] Although our study showed comparability between conservative and surgical managements in patients with grade IV blunt kidney trauma, the trend of mortality was more likely in the surgical group than in the conservative group. Based on this finding, several other studies have indicated the superiority of conservative management over surgical management.…”
Section: Discussionmentioning
confidence: 98%
“…27,28 In particular, blunt injury is more prevalent, accounting for 71%-95% of all trauma cases. 27,28 Deceleration injury in blunt trauma causes disturbances due to renal injury by the major surrounding attachment elements, such as renal pedicle and uretero-pelvic junction, whereas acceleration injury causes disturbances due to collision of the kidney with surrounding elements, such as the ribs and spine. 27,28 These two mechanisms lead to kidney injury with varying degrees of severity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation